CORONA VIRUS DISEASE-19 CLINICAL AND LABORATORY CHARACTERISTICS ASSOCIATED WITH DISEASE SEVERITY IN PATIENTS PRESENTING AT A TERTIARY CARE HOSPITAL OF PESHAWAR - Wajeeha Qayyum; Shaheen Ali Khan; Laraib Saeed; Mohammad Jawad; Muhammad Fozan Khan; Ullah, Ihsan (Journal of Ayub Medical College Abbottabad, 2021)
Background: Coronavirus disease-19 has a wide range of clinical presentations and varied outcomes. It is a new disease and researchers are trying to explore its clinical presentation and outcome to know more about the course of the disease. The objective of the present study was to determine the clinical and laboratory characteristics of Coronavirus disease-19 associated with severity of the disease. Methods: This cross-sectional study was conducted at Rehman Medical Institute, Peshawar from April to August 2020. All patients presented to the hospital and were diagnosed as COVID-19 were enrolled in this study. Disease characteristics and clinical outcomes were noted in both mild and severe cases. Patients were divided into 2 groups based on the disease severity and a comparison was made between these groups in terms of demographics, lab parameters and outcomes. Data were analysed by using SPSS version 24. Results: Out of 227 patients,80.2% (n=182) were males while 19.8% (n=45) were females. The mean age of the patients was 54.44±14.35 yrs. 61.2% (n=139) had co-morbidities with diabetes being the most common. 26.9%(n=61) had severe disease and 18.1% (n=41) died.20.7% (n=47) had lymphopenia ,48.45% (n=110) had leucocytosis and thrombocytopenia was seen in 11.89% (n=27). CRP, D-dimers, ferritin and LDH were raised in 83.25% (n=189), 80.17% (n=182), 81.05% (n=184), 77.09% (n=175) of the patients respectively. Comparing our designated patient groups revealed that old age, comorbidities, leucocytosis, lymphopenia, raised inflammatory markers were associated with severe disease and that mortality was high in the severe disease group. Conclusion: Middle-aged males with comorbidities were the most affected subset of patients. Disease severity was associated with old age, comorbidities and certain lab abnormalities. The outcome was poor in case of severe disease. However, no gender correlation was found with disease severity.